356 Clinical and Economic Benefits of Cervical Cancer Cotesting With Three- and Five-Year Intervals. (11th January 2018) - Lacey, Michael; Lenhart, Gregory; Miller, Jeffrey; Hilborne, Lee; Pohlman, Scott; Vilalta, Adrian; Troeger, Kathleen; Felix, Juan
Abstract: Objectives: To analyze clinical and economic benefits of cervical cancer screening using cotesting (cytology plus human papillomavirus [HPV] testing) with three- vs five-year intervals. Methods: Previously published economic, epidemiologic, and clinical data (Felix et al. J Women's Health . 2016) demonstrating benefits of cotesting over primary HPV screening were used to develop a health state transition (Markov) cost-utility model with a one-year cycling. A hypothetical cohort of 1 million women receiving cervical cancer screening at either three- or five-year intervals was simulated for 40 years (starting at age 30 years until age 70 years). Outcomes included invasive cervical cancer (ICC) cases, ICC-related deaths, costs (2016 USD), and quality-adjusted life years (QALYs). Comprehensive sensitivity analyses were performed. Results: Model analyses predicted 40% fewer ICC cases with a three-year cotesting interval compared with a five-year interval (57.61 vs 96.51 per 10, 000 women for three- and five-year intervals, respectively). ICC deaths were predicted to be 39% lower (23.06 vs 37.58 per 10, 000 women for three- and five-year intervals, respectively). Results for the three-year interval screening show a lifetime gain of 0.0201 QALYs (23.0084 QALYs vs 22.9883 QALYs for three- and five-year intervals, respectively). The cumulative increase in screening costs for three-year cotesting intervals (477 per woman over 40 years) was partially offset by cost savings (114) realized from cervical cancer prevention and reduced treatment cost. The modest net increase in total cost for three-year co-testing intervals (363) can be considered cost-effective compared with five-year cotesting based on an incremental cost-utility ratio (ΔCost/ΔQALY) of 18, 060 per QALY gained. Conclusions: Cervical cancer cotesting at three-year intervals is predicted to be a cost-effective approach to reducing the number of ICC cases and ICC deaths over currently recommended five-year intervals.